1997
DOI: 10.1136/jnnp.62.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracranial hypotension: MRI and radionuclide cisternography findings.

Abstract: Group 2 (weak to moderate staining) 15-5 (6 7) (n = 22) 16-1 (9 4) (n = 13)There were no significant differences between groups (Student's t test).gliomas, but failed to show a correlation with cell proliferation. Nor was the occa-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…10,17) MR imaging and MR myelography before and after RI cisternography on 10 patients with orthostatic headache found that 5 had lumbosacral CSF leaks after the lumbar puncture, whereas none showed CSF leaks before the puncture. 12) In 4 of the 5 patients with CSF leaks, RI cisternography showed lumbosacral CSF leaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,17) MR imaging and MR myelography before and after RI cisternography on 10 patients with orthostatic headache found that 5 had lumbosacral CSF leaks after the lumbar puncture, whereas none showed CSF leaks before the puncture. 12) In 4 of the 5 patients with CSF leaks, RI cisternography showed lumbosacral CSF leaks.…”
Section: Discussionmentioning
confidence: 99%
“…6) Both these disorders are thought to be caused by spontaneous CSF leakage, 16) so the presence of a CSF leak is important to prove if a treatment with an epidural blood patch is planned. 5,14) Radioisotope (RI) cisternography, 5,17) MR myelography, 19,21,23) spinal MR imaging, 4,11,22) computed tomography (CT) myelography, 14,15) and intrathecal gadolinium-enhanced MR myelography have been reported to show spinal CSF leaks. 1,20) This study proposes the occurrence of floating dural sac sign, which is observed as a hyperintense band or rim around the spinal dural sac on axial T 2 -weighted images (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It may be associated with nausea, vomiting, neck stiffness, horizontal diplopia, blurring of vision, photophobia, field defects, vertigo, tinnitus, dysgeusia, unilateral facial numbness, and weakness. [3567] Conservative methods like bed rest are the first line treatment. [8] If not effective, interventional methods like autologous epidural blood patch are used.…”
Section: Discussionmentioning
confidence: 99%
“…8). 13,40,50,62,63,70,71,79 In most cases, this study will show early accumulation of tracer in the kidneys and bladder, slow ascent along the spinal axis, and less activity than expected over the cerebral convexities. These findings suggest unusually rapid uptake of tracer into the bloodstream through the extensive epidural venous plexus.…”
Section: Radionuclide Cisternographymentioning
confidence: 94%
“…In some patients, particularly those who have not received specific treatment for their CSF leak, considerable clinical improvement is shown over time whereas their MR-documented abnormalities persist. 8,79 In most patients, the pachymeningeal enhancement is the first abnormality that resolves, whereas the brain sagging may linger for a considerably longer time or show only partial improvement. 56,71 …”
Section: Cerebral Mr Imagingmentioning
confidence: 99%